2018
DOI: 10.5395/rde.2018.43.e29
|View full text |Cite
|
Sign up to set email alerts
|

Do universal adhesives promote bonding to dentin? A systematic review and meta-analysis

Abstract: ObjectivesThe aims of this study were to conduct a systematic review of the microtensile bond strength (µTBS) of multi-mode adhesives to dentin and to perform a meta-analysis to assess the significance of differences in the µTBS of one of the most commonly used universal adhesives (Scotchbond Universal, 3M ESPE) depending on whether the etch-and-rinse or self-etch mode was used.Materials and MethodsAn electronic search was performed of MEDLINE/PubMed, ScienceDirect, and EBSCOhost. Laboratory studies that evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 33 publications
1
36
1
2
Order By: Relevance
“…However, for UAs, results from in vitro studies indicate that the adhesive strategy does not affect immediate dentin bonding. Meta‐analysis of in vitro studies by Elkaffas et al reported statistically similar average dentin μTBS values of about 37 MPa for ER versus 35 MPa for SE strategies. Rosa, et al meta‐analysis also did not find any statistically significant difference in the μTBS of UAs (SBU, GPB, PBE, and FBU) with the ER versus SE strategies.…”
Section: Resultsmentioning
confidence: 92%
“…However, for UAs, results from in vitro studies indicate that the adhesive strategy does not affect immediate dentin bonding. Meta‐analysis of in vitro studies by Elkaffas et al reported statistically similar average dentin μTBS values of about 37 MPa for ER versus 35 MPa for SE strategies. Rosa, et al meta‐analysis also did not find any statistically significant difference in the μTBS of UAs (SBU, GPB, PBE, and FBU) with the ER versus SE strategies.…”
Section: Resultsmentioning
confidence: 92%
“…As for fig. 2; failure probably started at the dentinadhesive interface as a corner flaw and propagated through the adhesive (31,32).So, the null hypothesis was rejected because each different etching mode created different weak regions at the interface between resin composite and adhesive layer or between adhesive layer and decalcified dentin; which varied according to the universal adhesive used.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning most universal adhesives, in vitro studies report consistently that a similar immediate dentin microtensile bond strength can be achieved using either the etch-and-rinse or the self-etch adhesive strategy while exhibiting a relatively high performance. 4,23 Nevertheless, when adhesive interfaces were subjected to aging processes, several studies concluded that the self-etch approach resulted in more stable long-term bond characteristics. 6,9,24 One meta-analysis of in vitro studies that evaluated nanoleakage related to universal adhesives reported divergent results and highlighted that etching modes influenced significantly and dissimilarly the nanoleakage of universal adhesives.…”
Section: Discussionmentioning
confidence: 99%
“…Scotchbond TM Universal contains 10-MDP as its acidic functional monomer and offers a low demineralization capacity. Its interaction with dentin is either micromechanical, through shallow but adequate dentin hybridization, 23,27 or chemical, through the establishment of a strong ionic bond between 10-MDP and calcium atoms within hydroxyapatite crystals, forming a highly organized layer of stable and low-soluble calcium-phosphate salts. 12,13 Nevertheless, recent findings demonstrate that the hybrid layer stability of resin-dentin bonds in 10-MDP-based adhesives has been wrongly attributed to the presence of these nanolayered structures with insoluble MDP-calcium salts.…”
Section: Discussionmentioning
confidence: 99%